The Effect of AR Assemblr Edu Media on Critical Thinking Skills on Food Web Material - Handayani, Diva Fithriya; Handayani, Sri Lestari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Critical thinking is one of the important 21st century skills developed at the elementary school level. However, students often struggle to understand ecosystem concepts such as food webs due to limited use of interactive learning media. This study contributes by integrating food web material and the development of critical thinking through Assemblr Edu-based Augmented Reality (AR) media. This study aims to examine the outcome of Assemblr Edu-based AR media on fifth-grade students’ critical thinking skills in learning food web. This study uses a quantitative method, namely a quasi-experimental design with a Pretest-Posttest Only Control Group. The participants consisted of 62 students of SDN Ciracas 07 Pagi. The sample technique used cluster random sampling, which involved randomizing existing classes rather than individuals. It was separated into two groups, 31 experimental students and 31 control students. An essay test was employed as the research instrument. It was established using five indications of critical thinking skills, namely Providing simple explanations, building basic skills, drawing conclusions, providing further explanation, and organizing strategies and tactics. The results of the independent sample t-test analysis showed that the two groups had a significant difference indicated by the significance value (sig. 0.048 <0.05). In addition, the effect size value of 0.513 is in the medium category. These findings suggest that Assemblr Edu-based AR media has a considerable impact on students’ critical thinking skills. However, the use of this medium requires the support of compatible devices, stable internet connection, and teacher assistance in using digital media.